Visual problems of new Malaysian drivers - Abdul Mutalib, Haliza; Md Mustafa, Md Muziman Syah; Mohammad Fadzil, Norliza (Academy of Family Physicians of Malaysia, 2010)
Purpose: The objective of this study was to determine the prevalence of poor visual acuity, colour blindness and visual field defect of new Malaysian drivers. Methods: A total of 3717 new drivers (50.2% males and 49.8% females) age 19±6 years, voluntarily participated in this study. Standard optometric apparatus such as LogMAR Charts, Ishihara plates and HandHeld Bernell Perimeter were used and standard procedures were applied. Results: The visual examination showed 6.7% (n=250) of subjects achieved less than 0.3 LogMAR with better eye whilst 2.2% (n=83) had failed the Ishihara Test (2.1% males and 0.1% females). Most of the affected drivers were deutranopia. Only 2094 subjects had their visual field using a mobile Handheld Bernell Perimeter. 1.72% (n=36) subjects have less than 120 degrees of peripheral field of vision. Conclusions: The visual status among new Malaysian drivers needs to be taken seriously to ensure safe driving. Other factors such as colour vision and visual field screening have to be considered seriously when evaluating the visual performance of a driver. Good visual performance is indispensible for safe driving.